Legal Canons. - Balkin, Jack (NYU Press, 2000)
Every discipline has its canon: the set of standard texts, approaches, examples, and stories by which it is recognized and which its members repeatedly invoke and employ. Although the last twenty-five years have seen the influence of interdisciplinary approaches to legal studies expand, there has been little recent consideration of what is and what ought to be canonical in the study of law today. Legal Canons brings together fifteen essays which seek to map out the legal canon and the way in which law is taught today. In order to understand how the twin ideas of canons and canonicity operate i.